The Long Non-coding RNA NEAT1/miR-224-5p/IL-33 Axis Modulates Macrophage M2a Polarization and A1 Astrocyte Activation - Liu, Dongliang; Wei, Yuehua; Liu, Yudong; Wu, Tianding; Hu, Jianzhong; Lu, Hongbin (Molecular neurobiology, 2021)
To identify potential regulators and investigate the molecular mechanism of macrophage polarization affecting astrocyte activation from the perspective of non-coding RNA regulation, we isolated mouse bone marrow mononuclear cells (BMMNCs)–induced macrophages toward M1 or M2a polarization. Long non-coding RNA NEAT1 and IL-33 expression levels were significantly upregulated in M2a macrophages; NEAT1 knockdown in M2a macrophages markedly reduced the protein levels of IL-33 and M2a markers, IL-4 and IL-13 concentrations, and the bacterial killing capacity of M2a macrophages. NEAT1 acted as a competing endogenous RNA (ceRNA) to regulate IL-33 expression by sponging miR-224-5p in M2a macrophages; NEAT1 knockdown upregulated miR-224-5p expression, while miR-224-5p inhibition increased the protein content and concentration of IL-33. miR-224-5p inhibition exerted the opposite effects on the protein levels of IL-33 and M2a markers, IL-4 and IL-13 concentrations, and the bacterial killing capacity of M2a macrophages compared to NEAT1 knockdown; the effects of NEAT1 knockdown were significantly reversed by miR-224-5p inhibition. M2a macrophage conditioned medium (CM) significantly suppressed the activation of A1 astrocytes. NEAT1 knockdown M2a macrophage CM led to enhanced A1 astrocyte activation while miR-224-5p–silenced M2a macrophage CM led to a blockade of A1 astrocyte activation; the effects of NEAT1 knockdown M2a macrophage CM on A1 astrocyte activation were significantly reversed by miR-224-5p inhibition in M2a macrophages. The NEAT1/miR-224-5p/IL-33 axis modulates macrophage M2a polarization, therefore affecting A1 astrocyte activation.